Studi Literatur: Pengalaman Menyusui pada Ibu Usia Remaja - Yanti Yanti; Irwan Taufiqur Rachman; Arista Kusuma Wardani (Jurnal Kesehatan Manarang, 2022)
Breastfeeding in one of the best ways to reduce infant mortality. However, UNICEF data in 2019 recorded that only 43% of newborns started breastfeeding in the first hour and 41% received exclusively breastfed. The causes of initiation and continuation of breastfeeding are closely related to the age of the mother. Adolescent mothers were found to not continue exclusive breastfeeding. This article aims to explore the experience of exclusive breastfeeding for adolescent mothers. The method used is a literature study. Research questions were identified using the PEOS (Population, Exposure, Outcome, Study Design) framework. The journals used in the literature review were obtained through the Pubmed, Science Direct and Google Scholar databases from 2010-2020. The keywords used according to MESH (Medical Subject Heading) are "experience", "exclusive breastfeeding", and "adolescent mothers", and selected full text. The results of the review of 6 articles include: mother’ decisions to breastfeed such as, breastfeeding is a natural, easy, and fun way, a supportive environment, breastfeeding can improve baby’s health, provide benefits for mothers, save costs. The obstacles faced by adolescent mother include, lack of knowledge and skills, uncontrollable and unplesant physical experiences, inadequate response to health services, lack of support for breastfeeding at work/school, and difficulty breastfeeding in public places. So, adolescent mothers need breastfeeding support such as information support, instrumental support, emotional support, and apraisal support.